The Interplay of Familial and Individual Risk in Predicting Clinical Improvements in Pediatric Anxiety Disorders. (21st December 2018) - Kiff, Cara J.; Ernestus, Stephanie; Gonzalez, Araceli; Kendall, Philip C.; Albano, Anne Marie; Compton, Scott N.; Birmaher, Boris; Ginsburg, Golda S.; Rynn, Moira; Walkup, John T.; McCracken, James; Piacentini, John
Abstract : Bioecological models of developmental psychopathology underscore the role of familial experiences of adversity and children's individual-level characteristics in heightening risk for pediatric anxiety through direct, combined, and interactive effects. To date, much of the existing research dedicated to pediatric anxiety disorders has largely been examined in bioecological models of diathesis-stress using community samples. This study extends our understanding of children's differential responsiveness to familial adversity by examining the diathesis-stress interaction of cumulative risk and children's individual-level vulnerabilities (negative affectivity and coping efficacy) within a clinic-referred treatment study for pediatric anxiety disorders. A cumulative risk index assessing exposure to familial adversity (e.g., socioeconomic status [SES], parent psychiatric illness) and self-reported measures of children's negative affectivity and coping efficacy were each measured at the intake of a randomized controlled clinical trial for the treatment of pediatric anxiety disorders ( N  = 488; 7–17 years of age). Trajectories of interviewer-rated anxiety symptoms were assessed across 12 weeks of treatment at baseline, 4 weeks, 8 weeks, and 12 weeks. Consistent with models of temperamental risk for mental health problems, negative affectivity predicted higher anxiety symptoms at intake. A significant diathesis-stress interaction between cumulative risk and coping efficacy emerged, as high risk and perceptions of lower coping efficacy attenuated declines in anxiety across 12 weeks. These patterns did not differ across treatment conditions. The results indicate that for youth experiencing high levels of stress, additional treatment efforts targeting familial stressors and coping efficacy may be important in maximizing treatment outcomes.